Administrative Inactivity: Concept and Requirements of Legality - Sergey V. Yarkovoy (Сибирское юридическое обозрение)
The general concept of omission in law, as well as the concept and main features of inactivity on the part of executive bodies, other public administration agencies and their officials in their administrative law enforcement are examined, conditions of legality of such inactivity are under study.